2014
DOI: 10.1186/2193-1801-3-296
|View full text |Cite
|
Sign up to set email alerts
|

Methods and protocol of a mixed method quasi-experiment to evaluate the effects of a structural economic and food security intervention on HIV vulnerability in rural Malawi: The SAGE4Health Study

Abstract: BackgroundPoverty and lack of a predictable, stable source of food are two fundamental determinants of ill health, including HIV/AIDS. Conversely, episodes of poor health and death from HIV can disrupt the ability to maintain economic stability in affected households, especially those that rely on subsistence farming. However, little empirical research has examined if, and how, improvements in people’s economic status and food security translate into changes in HIV vulnerability.MethodsIn this paper, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Furthermore, poverty has been found to have a complex relationship with HIV and to play a multidimensional role that is shaped by the broader social environment (Kim, Pronyk, Barnett, & Watts, 2008). Thus, researchers have increasingly called for multisectoral intervention packages that go beyond one structural factor to incorporate several that are appropriate to the local context, such as food security and property rights (Dworkin & Blankenship, 2009; Cohen et al, 2015; Dworkin et al, 2013; Kim et al, 2007; Weinhardt et al, 2009, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, poverty has been found to have a complex relationship with HIV and to play a multidimensional role that is shaped by the broader social environment (Kim, Pronyk, Barnett, & Watts, 2008). Thus, researchers have increasingly called for multisectoral intervention packages that go beyond one structural factor to incorporate several that are appropriate to the local context, such as food security and property rights (Dworkin & Blankenship, 2009; Cohen et al, 2015; Dworkin et al, 2013; Kim et al, 2007; Weinhardt et al, 2009, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive description of SAGE4Health methodology is described elsewhere [ 4 ]; a summary follows. SAGE4Health examines three interrelated samples designed to systematically evaluate the SAFE program, a community-based, structural, multilevel health and development intervention designed and implemented by CARE International-Malawi from January 2008–December 2010.…”
Section: Methodsmentioning
confidence: 99%
“…Interventions that break the cycle of poverty are of increasing interest to the development and public health communities given the potential for sustainable long-term impact. Our study [ 3 , 4 ] examines the effects of a structural multi-level HIV intervention, referred to as SAFE, designed and implemented by a large non-governmental organization (NGO), CARE International, in rural Malawi, which has high levels of poverty, food insecurity, and HIV prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…The first found that individual savings, either alone or in combination with other HES and sexual health support, did not increase self-reported testing uptake among adolescent girls in Uganda (Austrian & Muthengi, 2014). In the other, participants in a multi-component intervention including group savings in Malawi were nearly twice as likely to report having undergone HTS compared to a control group, though the study did not measure the association between HTS uptake and the savings component independently (Galvao, 2015;Weinhardt et al, 2014). No savings studies assessed an outcome related to linkage to care.…”
Section: Protection Interventionsmentioning
confidence: 99%
“…Only one study assessed HTS uptake among participants in an integrated agricultural training, group savings, and HIV and gender education intervention in Malawi, finding that participants in the combined intervention had nearly double the odds of reporting HTS uptake compared to a control group (Galvao, 2015;Weinhardt (Table 6). No studies assessed vocational or entrepreneurial training and linkage to care.…”
Section: Vocational and Entrepreneurial Trainingmentioning
confidence: 99%